IDIOMATIC EXPRESSIONS IN TAYLOR SWIFT’S SONGS ON THE ALBUM EVERMORE - Siti R Kondoalumang; Sanerita T. Olii; Maikel B. G. Sanger (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
This study aims at identifying and describing the idiomatic expressions found in Taylor Swift’s songs on the Evermore album. This study was a descriptive qualitative study that used note-taking and literature review as the means of collecting the data. The primary data of this study were taken from the lyrics of 4 songs in Taylor Swift’s Evermore album. The researcher also used secondary data such as academic articles, books, and various websites in conducting this study. The data were then analyzed using the content analysis technique proposed by Miles and Huberman. The result showed that there are 21 idioms found in Swift’s song lyrics in the Evermore album. Based on its types, there are 2 proverb idioms, 8 phrasal compound idioms, 9 tournures idioms, and 2 simile idioms. Those idiomatic expressions are used to express the problem in life and the problems in love faced by the character in the songs.